PENGARUH STRATEGI PELAKSANAAN KOMUNIKASI TERAPEUTIK TERHADAP RESIKO PERILAKU KEKERASAN PADA PASIEN GANGGUAN JIWA DI RUMAH SAKIT JIWA PROVINSI JAMBI - Vevi Suryenti Putri; Restia Mella N; Salvita Fitrianti (Universitas Baiturrahim, 2018)
Schizophrenic patients such as violent behavior violent behavior is a form of behavior that aims to injure a person physically and psychologically. To overcome violent behavior in schizophrenic patients it is necessary to take anticipatory strategies, in the form of therapeutic communication. The purpose of this study is to see whether there is an effect of therapeutic communication therapy on patients at risk of violent behavior in the Inpatient Room of Jambi Provincial Hospital. The study was conducted on 12-19 July 2018. The research design used was pre-experimental design with one group pre-test and post-test design. Respondents in this study were all schizophrenic patients with a risk of violent behavior in the inpatient ward of the Regional Psychiatric Hospital of Jambi Province as many as 98 people with a total sample of 20 respondents. Data collection was done by proportional random sampling technique. The results showed that before therapeutic communication therapy was known, most respondents had poor behavior (maladaptive) with a mean of 40.50, and therapeutic communication therapy was known to increase the score of behavior better (adaptive) with mean 43.90. The results showed that there was a significant effect of therapeutic communication therapy in addressing the problem of violent behavior in schizophrenic patients with a p-value of 0.013 (p-value <0.05).